Analysis of Students' Learning Problem Solving Skills through the Application of Polya's Steps - Amrullah, Amrullah; Chelladurai, Subathra; Zulihi, Zulihi; Ramdhani, Muhammad Iqbal; Sukma, Fitri Alya Okta; Patil, Atul Bansilal; Durgayan, Alesa (International Journal of Education Research and Development, 2024)
The purpose of this study was to describe the ability to solve learning problems in the Islamic education learning system planning course (PSPP) through Polya's steps (understand the problem, devise a plan, carry out the plan, and looking back), using a quantitative descriptive approach. The results showed that the use of Polya's steps was quite effective in solving learning problems in PSPP subjects. From the skill test, 4 categories of scores were obtained, namely students who obtained a score of 100 and a score scale of A amounted to 6 people with a percentage of 13.04%. While students who obtained a score of 95 with a value scale of A were 13 people with a percentage of 28.26%. Students who scored 90 with a grade scale B were 20 people with a percentage of 43.48%. While students who scored 75 with a grade scale C were 7 people with a percentage of 15.22%.